The reimagination of school-based physical activity research in the COVID-19 era. - Deirdre M Harrington; Michelle O'Reilly (PLoS Medicine)
Deirdre Harrington and Michelle O'Reilly discuss the article "Effectiveness and cost-effectiveness of the GoActive intervention to increase physical activity among UK adolescents: A cluster randomised controlled trial" by Kirsten Corder and colleagues.